2020
DOI: 10.1093/infdis/jiaa591
|View full text |Cite
|
Sign up to set email alerts
|

A Granulocytic Signature Identifies COVID-19 and Its Severity

Abstract: Background An unbiased approach of SARS-CoV-2-induced immune dysregulation has not been undertaken so far. We aimed to identify previously unreported immune markers able to discriminate COVID-19 patients from healthy controls and to predict mild and severe disease. Methods An observational, prospective, multicentric study was conducted in patients with confirmed COVID-19: mild/moderate (n=7) and severe (n=19). Immunophenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 30 publications
10
102
0
3
Order By: Relevance
“…Recent reports have indicated the increased number of immature neutrophils in severe forms of COVID-19. 29 - 31 Complementing these studies, we here provide evidence for impaired function of these cells in correlation with the severity of COVID-19.…”
Section: Discussionsupporting
confidence: 61%
“…Recent reports have indicated the increased number of immature neutrophils in severe forms of COVID-19. 29 - 31 Complementing these studies, we here provide evidence for impaired function of these cells in correlation with the severity of COVID-19.…”
Section: Discussionsupporting
confidence: 61%
“…Recent studies have also reported significant reduction in circulating LFA-1 expressing T lymphocytes [ 33 ], a significant increase in Mac-1 expression in monocytes [ 34 , 35 ], and a significant decrease of Mac-1 expression in granulocytes [ 36 ] in symptomatic COVID patients, but no confirmation on whether these cells were infected with SARS-CoV2. Both these observations could be consistent with our predictions and require further in vitro receptor binding assays coupled with histopathological studies from infected cells and tissues to robustly confirm the infectibility of SARS-CoV2 in LFA-1 and Mac-1 expressing cells, and the role of ORF7a in modulating LFA-1 and Mac-1 expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that patients infected with SARS-CoV-2 have a high neutrophil count during the severe phase, and the neutrophil to lymphocyte ratio can be used to predict the degree of disease severity in patients with early-stage COVID-19 [ 32 , 33 ]. SARS-CoV-2 infection is also characterized by changes in the frequency of granulocyte subsets and alteration of their functional phenotypes that correlate with COVID-19 severity [ 34 ]. Granulocytes and mainly their activated CD11b + subset were significantly increased during the active phase in the group of COVID-19 patients, while the CD11b − subset was diminished.…”
Section: Discussionmentioning
confidence: 99%